Tensile behavior of flax textile reinforced lime-mortar: Influence of reinforcement amount and textile impregnation. (May 2021) - Ferrara, Giuseppe; Pepe, Marco; Martinelli, Enzo; Tolêdo Filho, Romildo Dias
Abstract: Companies and practitioners working in the civil construction sector are more and more aware and motivated to develop and adopt sustainable building materials, possibly obtained from renewable and locally available resources. As part of this common effort, special attention is being paid to an emerging class of materials generally referred to as bio-based composite systems. In this context, this paper investigates the mechanical properties of a Textile-Reinforced Mortar (TRM) system produced with Flax textile embedded within a hydraulic lime-based mortar. The research aims at revealing the influence of either the reinforcement amount and the applied pre-treatment of the textile on the resulting tensile response and the cracking patterns exhibited by these TRM systems. The analysis of the results presented herein allows to have a comprehensive overview of the feasibility of using flax textiles for strengthening and retrofitting of existing structures.